INTEGRASI TASAWUF DALAM HUKUM KELUARGA ISLAM - Mochammad Arifin (SINDA: Comprehensive Journal of Islamic Social Studies, 2021)
Abstrac Knowledge is very important in a family, it is one of requirements to create a sakinah-mawadah-warohmah family. More than that, a religious understanding is expected to be guidance and standard in household lifestyles. Sufism is a complement from a religious perspective, with the synergy of sharia knowledge (Islamic law) and aqidah as an absolute unity. Study uses qualitative research methods with descriptive analytical research style. The study uses literature based on, journals, books, articles to support the research, which will be a moral support of Islamic family law nowadays. Then conducted investigations and studies that are relevant to the research, intend to revive the understanding about the importance of Sufism in an islamic household, which there are also national civil rules in it. The library approach is as analytical tool to dissect the integration between Sufism and islamic household lifestyles in a holistic and comprehensive way to create understanding and thoughts about the importance of Sufism in a family, that always relevant and becomes a guide to live a family life. The results show that the knowledge of Sufism can be a guidance, how to build an ideal household according to religion and as a way to receive God's pleasure. The implementation of this understanding is not easy to be applied considering the basic needs that must be fulfilled in a family, for example about economics, social and temporary interests. Therefore, it is necessary to get used to do good things according to Qur'an and Hadith as a filter and balancer in life.